PENINGKATAN LITERASI KEUANGAN BAGI SISWA SMA NEGERI 10 KOTA BENGKULU MELALUI EDUKASI KEUANGAN UNTUK MENDUKUNG INDEKS LITERASI KEUANGAN PROVINSI BENGKULU - Dion Raja Kusumah,; Kelfin Hardiansyah,; Hisyam Rahmatullah Akbar,; Arita Nurul Khotimah,; Nur El Hasanah,; Siska Yosmar, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Based on the low financial literacy index in Bengkulu Province, which is below the national average, this education program is designed to enhance financial understanding and skills within the community. Through the financial literacy education program, students are taught basic financial concepts, budget planning, debt management, simple investment, and consumer protection using guided modules. The implementation of the program showed a significant improvement in students' financial literacy understanding, as measured through engagement, questionnaires, and test scores. Collaboration between educational institutions, local government, and financial institutions played an important role in the success of this program. The results of the program show that SMA Negeri 10 Kota Bengkulu students have a better understanding of financial literacy, which is expected to help them manage their personal finances more wisely. The program provides not only theoretical understanding but also valuable practical experience. The program is expected to contribute to the improvement of the financial literacy index in Bengkulu Province, promoting the financial well-being of the community, and regional economic growth.